Estimates calculations algorithms in condition of huge dimensions of features' space - Kamilov, Mirzoyan; Fazilov, Shavkat; Mirzaev, Nomaz; Radjabov, Sobirjon (2012 IV International Conference Problems of Cybernetics and Informatics, 2012)
The problem of pattern recognition in condition of huge dimensions of features' space is considered. Extended model of recognition algorithms on the base of estimates' calculations algorithm is proposed.